Jump assist device cooperating with human using Scott-Russell mechanism - Takuma KAWAKAMI; Yuki NISHIJIMA; Keisuke YAGI; Yoshikazu MORI (Nihon Kikai Gakkai ronbunshu, 2025)
Various devices have been developed in recent years to assist human jumping using plate springs, rubber tubes, and other means. Nevertheless, using products of many kinds is difficult because they generate jumping force with human ankles fixed. Cooperating with human users is favorable for enhancing both usability and jumping height. Some researchers have adopted this approach. Unfortunately, the jumping height remains insufficient. As described in this paper, we have developed devices of two types that emphasize cooperation with the human user: a rotational model and a linear model. The former, which is used for comparison purposes, provides floor reaction force using a rotational mechanism similarly to a human ankle joint. The latter provides normal force using the Scott–Russell mechanism, which moves in the vertical direction. Moreover, this mechanism enables the user to generate floor reaction force for a longer duration. Experimentation demonstrated that the jumping height with the linear model increased by approximately 0.8 – 35% (0.4 – 12.4 cm) compared to that without a device. Moreover, the duration generating the jumping force when using the linear model increased by approximately 34% compared to that obtained when using the rotational model.